Heat Stress Impacts and Public Health Adaptation Strategies in Tropical Regions: A Narrative Review - Asnita Yani; Dewi Astuti Pasaribu; Siska Tri Darmanita Lase (Universitas Prima Indonesia, 2026)
Global climate change is intensifying heat stress and environmental degradation, posing a growing threat to public health in tropical regions such as Indonesia. This narrative review synthesizes evidence on the clinical, occupational, and epidemiological impacts of heat stress, identifies vulnerable populations, and outlines environmental health adaptation strategies in tropical settings. A literature search of Google Scholar, PubMed/MEDLINE, and ScienceDirect (2020–2026) identified 379 records, of which 10 peer-reviewed studies met the predefined eligibility criteria following a two-stage screening process and were retained for narrative synthesis. The reviewed evidence suggests that heat stress is associated with elevated mortality risk among vulnerable groups, particularly older adults and young children, and with dehydration and subjective health complaints among outdoor workers. Climate-related environmental changes were also associated with shifts in the transmission of dengue fever and diarrheal disease. Effective adaptation appears to require integrated occupational health protection, environmental sanitation, disease surveillance, health education, and community-based interventions. Although Green Open Spaces (GOS) were not directly evaluated in the included studies, this measure is discussed with reference to the broader environmental health literature as a complementary strategy for reducing heat exposure. These findings underscore the need to embed climate-sensitive adaptation measures within environmental and public health policy to strengthen population resilience in tropical regions.